g={(-9, 0), (-3, 2), (2, -9), (5, 6)} ; h= ( x )= 2x + 9

Calculus
Tutor: None Selected Time limit: 1 Day

May 11th, 2015

h-1x= 2x+9 -x

       =x+9

h^2-11 = (2x+9)^2 -11

            =4x^2+36x +91 -11

            =4x^2 +36x+80


is that g-12????

please check it

May 11th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
May 11th, 2015
...
May 11th, 2015
May 30th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer